The Differential Effects of Noneconomic Damage Cap Levels on Medical Malpractice Insurers. Issue 2 (1st July 2013) - Born, Patricia; Neale, Faith Roberts
Abstract This study examines the effect of tort reform on medical malpractice insurers with an emphasis on the effect of cap levels on noneconomic damages. While previous research finds that caps on noneconomic damages have a beneficial effect on insurer performance, these studies do not evaluate the effects of caps of varying size. Examining insurer data from 1997 to 2007, we test whether cap levels matter. We find that insurer performance generally improves when the cap is set at $250, 000, but caps exceeding $250, 000 are not associated with improved performance, as they are possibly not binding on award amounts.